Reduction of COVID-19 Anxiety Levels Through Relaxation Techniques: A Study Carried Out in Northern Spain on a Sample of Young University Students - Ozamiz-Etxebarria, Naiara; Santamaría, María Dosil; Munitis, Amaia Eiguren; Gorrotxategi, Maitane Picaza (Frontiers in Psychology, 2020)
Since March 14, 2020, Spain has been in a state of alarm, due to the crisis created by the outbreak of COVID-19. This measure has led to strict levels of lockdown. This situation has led to an increase in anxiety levels among the younger population. For this reason, an intervention was carried out with university voluntary participants in order to help lower their anxiety levels. Specifically, a telematic workshop was implemented to teach emotional literacy and relaxation techniques combined with the practice of the techniques in an autonomous manner. Anxiety measurements were taken before and after the workshop using the GAD7 scale. The results show that Jacobson's progressive relaxation techniques, Schultz's autogenous relaxation, abdominal relaxations and visualizations are effective in lowering the anxiety levels of university students being an alternative to pharmacotherapy.